Managerial Quality and Risk of Depressive Disorders Among Danish Eldercare Workers: A Multilevel Cohort Study. Issue 2 (February 2018) - Rugulies, Reiner; Jakobsen, Louise M.; Madsen, Ida E.H.; Borg, Vilhelm; Carneiro, Isabella G.; Aust, Birgit
Abstract : Objective: To examine whether low managerial quality predicts risk of depressive disorders. Methods: Using multilevel mixed-effects logistic regression analyses we examined the prospective association of individual-level and workplace-mean managerial quality with onset of depressive disorders among 5244 eldercare workers from 274 workplaces during 20 months follow-up. Results: Low managerial quality predicted onset of depressive disorders in both the individual-level (odds ratio [OR] = 1.85, 95% confidence interval [CI] = 1.25 to 2.76) and the workplace-mean analysis (OR = 1.48, 95% CI = 1.06 to 2.07). Low individual-level managerial quality predicted onset of depressive disorders when workplace-mean managerial quality was high (OR = 3.10, 95% CI = 1.71 to 5.62) but not when it was low (OR = 1.07, 95% CI = 0.61 to 1.87). This interaction was statistically significant ( P  = 0.03). Conclusions: Both low individual-level and low workplace-mean managerial quality predicted risk of depressive disorders. The association was strongest among individuals reporting low managerial quality at workplaces with high workplace-mean managerial quality.